Safety assessment of the SESAR operational concept - European air traffic management in 2020 and beyond - Fowler, D; Perrin, E; Pierce, R (4th IET International Conference on System Safety 2009. Incorporating the SaRS Annual Conference, 2009)
A related, theoretical paper for the same conference explains why a new approach, both broader and more rigorous than that traditionally followed in ATM, is needed for the safety assessment of new operational and technology changes, and presents the theoretical basis for what is an argument-driven "systems-engineering approach" This paper builds on that approach and describes how it is being applied to preliminary work on the massive changes that are planned for introduction into European ATM over the period up to 2020 and beyond, under the SESAR Programme. This preliminary work, closely related to European Commission initiated Episode 3 (EP3) project, is aimed at validating the approach as well as beginning to identify ways to maximize ATM contribution to aviation safety under the SESAR concept of operations. (8 pages)